2021
DOI: 10.1111/rda.13920
|View full text |Cite
|
Sign up to set email alerts
|

scRNA‐seq of ovarian follicle granulosa cells from different fertility goats reveals distinct expression patterns

Abstract: The new technology of high‐throughput single‐cell RNA sequencing (10 × scRNA‐seq) was developed recently with many advantages. However, it was not commonly used in farm animal research. There are few reports for the gene expression of goat ovarian follicle granulosa cells (GCs) during different developmental stages. In the current investigation, the gene expression of follicle GCs at different stages from two populations of Ji'ning grey goats: high litter size (HL; ≥3/L; 2 L) and low litter size (LL; ≤2 /L; 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
(37 reference statements)
2
23
0
Order By: Relevance
“…As described above, focusing on the CG methylation context of DMGs, and we found that the common DMGs were significantly enriched in the TGF-β and Wnt signaling pathways, which have been confirmed to be involved in fecundity (Chu et al, 2007;Gao et al, 2020). For example, INHBA is associated with follicle development (Cui et al, 2020;Li et al, 2021), oocyte maturation (Tesfaye et al, 2009) and fecundity (Hiendleder et al, 1996;Yu et al, 2019). In the present study, INHBA was found to contain five distal intergenic DMRs, with four DMRs being hyper-methylated and one being hypo-methylated in the LPB + vs. HPBB group.…”
Section: Discussionmentioning
confidence: 52%
“…As described above, focusing on the CG methylation context of DMGs, and we found that the common DMGs were significantly enriched in the TGF-β and Wnt signaling pathways, which have been confirmed to be involved in fecundity (Chu et al, 2007;Gao et al, 2020). For example, INHBA is associated with follicle development (Cui et al, 2020;Li et al, 2021), oocyte maturation (Tesfaye et al, 2009) and fecundity (Hiendleder et al, 1996;Yu et al, 2019). In the present study, INHBA was found to contain five distal intergenic DMRs, with four DMRs being hyper-methylated and one being hypo-methylated in the LPB + vs. HPBB group.…”
Section: Discussionmentioning
confidence: 52%
“…Dazl ( Bachvarova et al, 2004 ; Li et al, 2016 ; Bertho et al, 2021 ) was highly expressed in early oogonia, while the mitotic marker rad50 ( Kostyrko et al, 2015 ; Völkening et al, 2020 ; Liu et al, 2021 ) was mainly expressed in mitotic oogonia ( Figure 1D ). In addition, we identified somatic cells based on the following markers: follicle cells ( foxl2 , amh and hsd17b1 ) ( Pisarska et al, 2011 ; Luo et al, 2020 ; Moolhuijsen and Visser, 2020 ; Li et al, 2021 ), endothelial cells ( fli1 and fn1a ) ( Nagai et al, 2018 ; Wu et al, 2021 ), T cells ( cd2 , cd247 and cd28 ) ( Hurley et al, 1994 ; Lundholm et al, 2010 ), macrophages ( cd68 , epx and mmp9 ) ( Hunyady et al, 1996 ; Sendler et al, 2018 ) and erythrocytes ( alas2 ) ( Munday et al, 2000 ; Tsang et al, 2017 ) ( Figure 1E ). The top 20 differentially expressed genes (DEGs) in each cell were shown in Supplementary Figure S1D .…”
Section: Resultsmentioning
confidence: 99%
“…The expression of INHBA is also detected in the cumulus and mural granulosa cells in sinus follicles [ 38 ]. Li et al postulated that INHBA is expressed at different follicular stages and has extremely high expression in the GCs growth period in multiparous-lamb goat population [ 39 ]. Notably, mutations in the INHBA gene have a significant effect on the litter size of sheep [ 34 ], thus further verifying that it can affect the lambing performance of goats by regulating the development of follicles.…”
Section: Discussionmentioning
confidence: 99%